Correlation of Friesinger Score of Angiographic Severity of Coronary Artery with or without Hyperuricaemia among Acute Coronary Syndrome Patients (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Angiographic severity of coronary artery is essential to correlate with serum uric acid among acute coronary syndrome patients.Objective: The purpose of the present study was to correlate the Friesinger Score of angiographic severity of coronary artery with or without hyperuricaemia among acute coronary syndrome patients.Methodology: This cross-sectional study was carried out in the Department of Cardiology at National Institute of Cardiovascular Diseases, Dhaka, Bangladesh during the period of December 2011 to November 2012. Patients who were newly diagnosed as acute coronary syndrome during admission undergoing coronary angiography in National Institute of Cardiovascular Diseases, Dhaka during the specified period of time were the study population. Coronary angiography was done within 4 weeks after hospital admission. Study subjects were divided into two groups on the basis of serum uric acid levels. Patients who were newly diagnosed as acute coronary syndrome having normal serum uric acid levels (6mg/dl in women) were included in group II.Results: A total number of 103 patients were recruited for this study who were divided into two groups and 53 patients having normal serum uric acid were considered in group I and 50 patients having hyperuricaemia acid were considered in group II. The mean age of study subjects among group I and group II are 50.45±10.33 years and 52.98±10.559 years respectively. The value of stenosis in Friesinger score in group II (9.30±3.955) was remarkably higher than that of group I (3.77±3.43) and it was statistically highly significant (p=0.001). Here, the vessel score is also markedly higher in group II (2.14±0.83) than that of group-I (0.77±0.75) (p=0.001). The Pearson's correlation coefficient (r) was 0.288 which was significant (p< 0.037).Conclusion: In conclusion it showed that there was a positive linear correlation between Friesinger scores and normal level of serum uric acid.Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):60-64